Dynamic Pricing with Uncertain Capacities - Garcia, Daniel; Janssen, Maarten C. W.; Shopova, Radostina (Management Science, 2023)
In markets, such as those for airline tickets and hotel accommodations, firms sell time-dated products and have private information about unsold capacities. We show that competition under private information may explain observed phenomena, such as increased price dispersion and higher expected prices toward the deadline. We also show that private information severely limits the market power of firms and that information exchange about capacity increases firms’ profits. Finally, we inquire into the incentives to unilaterally disclose information or to engage in espionage about rival’s capacity and show that they increase firms’ profits compared with the private information setting. This paper was accepted by Omar Besbes, revenue management and market analytics. Funding: This work was partially funded by the Austrian Science Foundation FWF under [Project FG 6]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4613 .